Predicting Successful Trial of Labor after Cesarean Delivery: Evaluation of Two Scoring Systems Flamm And Grobman - Singh, Prachi; Gupta, Nimisha; Agarwal, Shikha; Acharya, Rajeev; Kumari, Richa (Journal of Neonatal Surgery, 2025)
Background:The chances for success vaginal birth after caesarean section (VBAC) vary significantly on the basis of patient’s demographic characteristics and obstetric history and attempting vaginal birth after cesarean section (VBAC) increases the risk of obstetric complications. However, the chance of successful vaginal birth after cesarean (VBAC) can be predicted using Trial of labor after cesarean (TOLAC) calculators, based on the patient’s pre-existing demographic and clinical factors. Objective: To predict successful trial of labor after cesarean delivery using two calculators: FLAMM and the Grobman calculator, and to compare the performance of the two calculators in successfully predicting VBAC. Methods: A Prospective cohort study in subjects with previous one lower segment caesarean section, admitted to LR, fulfilling the inclusion criteria, scoring was done under two study VBAC calculator and mode of delivery was studied. Results: A total of 200 subjects with previous one caesarean section were enrolled. One hundred fifty-two subjects consented for TOLAC, 103 (67.8%) underwent successful trial of vaginal birth, and 49 (32.2%) required cesarean section. Sensitivity and specificity were recorded for both the scoring systems, at a cutoff score of 5, the sensitivity of the FLAMM score was 71.84% and specificity was 75.51%. For the Grobman calculator, sensitivity (84.47%) and specificity (46.94%) were seen at a cutoff score of 70%. Conclusion: Patient specific chances of success vaginal birth after previous caesarean section can be predicted by the use of these prediction models. Both, FLAMM and Grobman et al. prediction models are easy to use and could successfully estimate the chances of vaginal birth after previous caesarean, in this study. The decision for women opting for TOLAC can be individualized, which can help in reducing feto-maternal complications.